SP5.2.2 A Systematic Review of Living Kidney Donor Enhanced Recovery After Surgery. (28th October 2021) - Byrne, Matthew; Mehmood, Ahmed; Summers, Dominic; Hosgood, Sarah; Nicholson, Michael
Abstract: Background: Enhanced recovery after surgery (ERAS) reduces complications and shortens hospital stays without increasing readmission or mortality. However, its role in living donor nephrectomy has not yet been defined. This systematic review aimed to describe the literature on ERAS in live donor nephrectomy. Methods: Medline, Embase, CINAHL, PsycINFO, and Cochrane Central were searched prior to 1/7/19 for all original randomised control and cohort studies relating to ERAS in living donor nephrectomy. The study was registered on PROSPERO (CRD: CRD42019141706). Results: 1248 patients were identified from 14 studies (630 patients with ERAS and 618 patients without). There were considerable differences in the protocols used and compliance with general ERAS recommendations was poor. Meta-analysis revealed that with ERAS length of stay significantly reduced by 0.83 days (95% CI = 0.30-1.37, p = 0.002), there was a trend towards decreased readmission (OR = 0.45, 95% CI = 0.19=1.10, p = 0.08), and there was no significant difference in complications (OR = 0.73, 95% CI 0.16-3.39, p=0.69). Opiate usage was significantly reduced with ERAS in all studies that measured it and there was no significant difference in creatine clearance. Conclusions: ERAS in live donor nephrectomy significantly reduces length of stay, and reduces opiate usage, without increasing readmission, complications, or creatinine. There is considerable variation in ERAS protocols used and a guideline for ERAS in live donor nephrectomy should be developed.